Peran Community Learning Center (CLC) dalam Meningkatkan Budaya Literasi pada Kalangan Dewasa di Perpustakaan Provinsi Jawa Tengah - Ambarwati, Septiana; El-Fikri, Dewi Nabela Sofya; Aini, Dewi Khurun (CV. Ulil Albab Corp, 2024)
Literacy culture is an important aspect in developing quality human resources. However, in Indonesia, the literacy rate is still low, especially among adults. To overcome this problem, Community Learning Center (CLC) plays a key role in promoting literacy culture in society. This study aims to analyze Community Learning Center (CLC) in improving literacy culture among adults in the Central Java Provincial Library. This study is a type of qualitative research using a survey method. Data collection was carried out through interviews and observations. Data obtained through interviews and observations were then analyzed through data reduction, then after that data presentation was carried out until the last was drawing conclusions and verification. The results of the study indicate that Community Learning Center (CLC) plays a role in improving literacy culture among adults in the Central Java Provincial Library. The Central Java Provincial Library provides various programs and services so that it can provide wider access in supporting the development of literacy among adults in the Central Java Provincial Library